Estradowa kronika filmowa. (Gdynia : [s.n.], 1955)
Afisz inf. o występach 22-28.11.1955 r. w gdyńskim kinie Atlantic.
Keywords: Kina -- Polska -- Gdynia -- 1945-1970 -- druki ulotne; Gdynia (Polska) -- 1945-1970 -- druki ulotne; Gdynia (Polska) -- 1945-1970 -- życie artystyczne